Covidscapes the pandemic in the Philippines - Aguilar, Filomeno V., Jr.
"This introductory essay develops the notion of Covidscapes, taking a cue from Arjun Appadurai. Despite mutations, a single type of coronavirus has gone around the world causing the Covid-19 disease. yet experiences with the pandemic have varied widely across and even within countries for reasons that go beyond the pathogen. The concept of Covidscapes captures the simultaneous sharing of a global phenomenon along with diversity and difference. Covidscapes are profoundly perspectival and disjunctive. State-societal factors suggest countries can have their own Covidscapes. The contributions in this issue shed light on the peculiar dynamics and contradictions of the Philippine Covidscape."
Keywords: COVID-19 -- Viruses; COVID-19.